FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI UMKM DI KAWALU, KOTA TASIKMALAYA - Heru Kurniawan; Rendy Sudirman (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
This study aims to find out the conditions and performance effectiveness of MSMEs in Kawalu District, Tasikmalaya City. By using factors that can affect performance in the scope of MSMEs in Kawalu District through a descriptive quantitative research method on 15 MSME companies that have 231 employees. The results showed that 50% of the performance factors could not be fulfilled by the company, while 50% of the performance factors could be fulfilled perfectly by MSME companies in Kawalu District.